ECONOMIC GROWTH AND ITS FACTORS ON THE EXAMPLE OF POLISH ECONOMY IN 2003-2009 (Research Bulletins of the Faculty of Economic Sciences, 2021)
Economic growth is an important issue and an important component of macroeconomic public finance. Its level depends on several factors that were analyzed in this article on the example of the Polish economy.
Keywords: economic growth, factors of economic growth, foreign trade, direct in-vestment, unemployment